Joining of tungsten to CuCrZr alloy with Cu-TiH2-Ni filler and Cu interlayer. (February 2019) - Peng, Shaoxue; Mao, Yangwu; Min, Mei; Xi, Lixia; Deng, Quanrong; Wang, Geming; Wang, Shenggao
Abstract: Joining of refractory tungsten to CuCrZr alloy has been performed using Cu-TiH2 -Ni filler and Cu interlayer at 1203 K. Microstructure characterization of the joint with Cu-TiH2 -Ni filler reveals a satisfactory interfacial bonding. The filler layer is composed of Cu solid solution, TiCu4, Ti2 (Cu, Ni), τ1 -Ti(Cux Ni1-x )2 and TiCu phases. The diffusion of W atoms from the W substrate into the filler layer occurs due to its high affinity with Ni in the filler. For the joint obtained with Cu-TiH2 -Ni filler and Cu interlayer, the favorable bonding is achieved and similar phase compositions of the filler layers are developed as that obtained with Cu-TiH2 -Ni filler. The thickness of Cu interlayer is reduced by about 50% owing to its dissolution into the molten filler. The microhardness distributions of the joints are highly related to the phases developed during brazing. The decrease in the hardness on the W side of the joint is attributed to the formation of vacancies in the W substrate. The joining strength of the joint obtained with Cu-TiH2 -Ni filler and Cu interlayer is higher than that without Cu interlayer, implying that the application of Cu interlayer is beneficial for the residual stress relaxation of the joint and the improvement of the joint strength. Highlights: W/CuCrZr joints were obtained using Cu-TiH2 -Ni filler and Cu interlayer at 1203 K. W atoms diffusion from W substrate into the filler layer occurs due to its high affinity with Ni. Hardness decrease in W side is attributed to vacancy formation due to unilateral diffusion of W. Thickness of Cu interlayer is reduced by about 50% owing to its dissolution into molten filler. Application of Cu interlayer contributes to stress relief and strength improvement of joint.